Zeolites as Ingredients of Medicinal Products - Iane M. S. Souza; Fátima García-Villén; César Viseras; Sibele B. C. Pergher (MDPI AG, 2023)
Development of new medicinal products for particular therapeutic treatment or for better manipulations with better quality and less side effects are possible as a result of advanced inorganic and organic materials application, among which zeolites, due to their properties and versatility, have been gaining attention. This paper is an overview of the development in the use of zeolite materials and their composites and modifications as medicinal products for several purposes such as active agents, carriers, for topical treatments, oral formulations, anticancer, the composition of theragnostic systems, vaccines, parenteral dosage forms, tissue engineering, etc. The objective of this review is to explore the main properties of zeolites and associate them with their drug interaction, mainly addressing the advances and studies related to the use of zeolites for different types of treatments due to their zeolite characteristics such as molecule storage capacity, physical and chemical stability, cation exchange capacity, and possibility of functionalization. The use of computational tools to predict the drug-zeolite interaction is also explored. As conclusion was possible to realize the possibilities and versatility of zeolite applications as being able to act in several aspects of medicinal products.